ON (3,2,ρ)-METRIZABLE SPACES - Čalamani, Sonja; Dimovski, Dončo; Seweryn-Kuzmanovska, Marzanna (Matematichki Bilten, 2016)
For a given \((3,2,ρ)\)-metric \(d\) on a set \(M\), we show that any \((3,2,ρ)\)-S-K-metrizable space has an open refinement which is both locally finite and \(σ\)-discrete.